Cholesterol derivative-based liposomes for gemcitabine delivery: preparation, in vitro, and in vivo characterization. (2nd December 2017) - Li, Tang; Chen, Li; Deng, Yihui; Liu, Xinrong; Zhao, Xiaoyun; Cui, Yiwen; Shi, Jia; Feng, Rui; Song, Yanzhi
Abstract: As an anti-tumor drug, gemcitabine (Gem) is commonly used for the treatment of non-small cell lung cancer and pancreatic cancer. However, there are several clinical drawbacks to using Gem, including its extremely short plasma half-life and side effects. To prolong its half-life and reduce its side effects, we synthesized a derivative of Gem using cholesterol (Chol). This derivative, called gemcitabine-cholesterol (Gem-Chol), was entrapped into liposomes by a thin-film dispersion method. The particle size of the Gem-Chol liposomes was 112.57 ± 1.25 nm, the encapsulation efficiency was above 99%, and the drug loading efficiency was about 50%. In vitro studies revealed that the Gem-Chol liposomes showed delayed drug release and long-term stability at 4 °C for up to 2 months. In vivo studies also showed the superiority of the Gem-Chol liposomes, and compared with free Gem, the Gem-Chol liposomes had longer circulation time. Moreover, an anti-tumor study in H22 and S180 tumor models showed that liposomal entrapment of Gem-Chol improved the anti-tumor effect of Gem. This study reports a potential formulation of Gem for clinical application.